2021
DOI: 10.1111/cea.14013
|View full text |Cite
|
Sign up to set email alerts
|

Sputum microRNA‐screening reveals Prostaglandin EP3 receptor as selective target in allergen‐specific immunotherapy

Abstract: Background Several microRNAs (miRs) have been described as potential biomarkers in liquid biopsies and in the context of allergic asthma, while therapeutic effects on the airway expression of miRs remain elusive. In this study, we investigated epigenetic miR‐associated mechanisms in the sputum of grass pollen‐allergic patients with and without allergen‐specific immunotherapy (AIT). Methods Induced sputum samples of healthy controls (HC), AIT‐treated and ‐untreated grass pollen‐allergic rhinitis patients with (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 76 publications
1
28
0
Order By: Relevance
“…As it was not possible to reveal all bronchiectasis‐related changes on the basis of FEV1 and FVC, the present observations are consistent with previously published data 35 . Patients with concomitant bronchiectasis but normal FEV1 and FVC, however, showed either a MEF25 below 50% or a significantly increased inflammatory cell load in the sputum (leucocyte number per mL sputum) 28,29 accompanied by high neutrophil numbers.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…As it was not possible to reveal all bronchiectasis‐related changes on the basis of FEV1 and FVC, the present observations are consistent with previously published data 35 . Patients with concomitant bronchiectasis but normal FEV1 and FVC, however, showed either a MEF25 below 50% or a significantly increased inflammatory cell load in the sputum (leucocyte number per mL sputum) 28,29 accompanied by high neutrophil numbers.…”
Section: Discussionsupporting
confidence: 87%
“…or a significantly increased inflammatory cell load in the sputum (leucocyte number per mL sputum) 28,29 accompanied by high neutrophil numbers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ILC2 regulation involves negative regulatory signals from IFNγ or PGE 2 ( Duerr et al, 2016 ; Maric et al, 2018 ; Zhou et al, 2018 ; Zhou et al, 2020 ). While PGE 2 inhibits ILC2 expansion through its receptors EP2 and EP4 ( Maric et al, 2018 ; Zhou et al, 2018 ), PGE 2 may also enhance ILC2 pro-inflammatory effector functions through EP3 ( Jakwerth et al, 2021 ). Additional studies are needed to better understand why Th2 cells, and potentially other type 2 immune cells, persist in the MA but not OVA model.…”
Section: Discussionmentioning
confidence: 99%
“…3 Little is known of how allergenspecific immunotherapy (AIT) affects local miRs and levels of corresponding gene transcripts of asthma patients. The study conducted by Jakwerth et al 4 identified miR-3935 as one of the most relevant out of four miRs up-regulated in asthmatics undergoing AIT, as its target PTGER3, the prostaglandin EP3 receptor, was downregulated compared to untreated asthmatics. Subsequently, sputum supernatants obtained from asthmatics contained elevated levels of its ligand PGE2 and ILC2 numbers compared to the AIT-treated group.…”
mentioning
confidence: 99%